Polish Interstate Relations with Ukraine, Belarus and Lithuania After 1990 in the Context of the Situation of National Minorities - Barwiński, Marek (European Spatial Research and Policy, 2013)
When we compare the contemporary ethnic structure and national policy of Poland and its eastern neighbours, we can see clear asymmetry in both quantitative and legal-institutional aspects. There is currently a markedly smaller population of Ukrainians, Belarusians and Lithuanians living in Poland than the Polish population in the territories of our eastern neighbours. At the same time, the national minorities in Poland enjoy wider rights and better conditions to operate than Poles living in Ukraine, Belarus and Lithuania. Additional complicating factor in bilateral relations between national minority and the home state is different political status of Lithuania, Belarus and Ukraine and different processes of transformation the consequence of which is differentiated state of political relations of Poland with its eastern neighbours. Lithuania, like Poland, is a member of EU, Ukraine, outside the structures of European integration, pursued a variable foreign policy, depending on the ruling options and the economic situation, and Belarus, because of internal policy which is unacceptable in the EU countries, is located on the political periphery of Europe.